High‐Throughput Micromechanical Testing Enabled by Optimized Direct Laser Writing. Issue 7 (5th June 2022) - Jelinek, Alexander; Zak, Stanislav; Alfreider, Markus; Kiener, Daniel
Abstract : Direct laser writing by two‐photon lithography enables the manufacturing of tailored 3D objects, commonly referred to as 3D‐printing, with submicrometer precision. Thereby, new approaches are enabled for miniaturized optical and mechanical devices, where basic material properties act as design guideline and initial input for finite element simulation‐driven device design. These mechanical properties are accessible through micromechanical testing and suitably adapted miniaturized specimens. With direct laser writing, a micromechanical specimen geometry can be readily manufactured without additional postprocessing, enabling the possibility of repetitive sample production and further high‐throughput testing. Widely overhanging features, as in common bending beam or tension specimens, easily cause floating layers as writing artifacts and thereby undefined geometries. Within this work, an approach to overcome this issue is presented. By introducing a slight taper within the geometry at initially printed layers, a reliable sample geometry is achievable without changing the overall mechanical behavior. As showcase geometries, miniaturized notched cantilever and advanced push‐to‐pull devices incorporating a notched tension specimen are detailed. Mechanical testing is conducted in situ and ex situ, and the mechanical influence from introducing a taper to a straight geometry is assessed via a finite element modeling. Thereby, a comprehensive approach for high‐throughput micromechanical testing is established. Abstract : The manufacturing of specimens for micromechanical testing requires optimization due to printing artifacts at widely overhanging features. Via introduction of a taper at down‐facing faces these can be overcome in order to obtain reproducible geometries, enabling high‐throughput sample testing of miniaturized fracture specimens in the terms of notched cantilever or push‐to‐pull notched tension geometries.